2010
DOI: 10.2337/db10-0281
|View full text |Cite
|
Sign up to set email alerts
|

FTO Is Increased in Muscle During Type 2 Diabetes, and Its Overexpression in Myotubes Alters Insulin Signaling, Enhances Lipogenesis and ROS Production, and Induces Mitochondrial Dysfunction

Abstract: OBJECTIVEA strong association between genetic variants and obesity was found for the fat mass and obesity-associated gene (FTO). However, few details are known concerning the expression and function of FTO in skeletal muscle of patients with metabolic diseases.RESEARCH DESIGN AND METHODSWe investigated basal FTO expression in skeletal muscle from obese nondiabetic subjects and type 1 and type 2 diabetic patients, compared with age-matched control subjects, and its regulation in vivo by insulin, glucose, or ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 42 publications
(75 reference statements)
3
76
1
Order By: Relevance
“…30 In type 2 diabetes, FTO was increased in the muscle, which altered insulin signaling, enhanced lipogenesis and reactive oxygen species production, and induced mitochondrial dysfunction in myotubes. 31 Intraperitoneal glucose injection reduced hepatic FTO mRNA levels in mice, but there were positive correlations between hepatic FTO mRNA expression and gluconeogenic gene expression. 32 This positive correlation was supported by another study, which also demonstrated that FTO mRNA was negatively associated with fat mass in skeletal muscle.…”
Section: Introductionmentioning
confidence: 90%
“…30 In type 2 diabetes, FTO was increased in the muscle, which altered insulin signaling, enhanced lipogenesis and reactive oxygen species production, and induced mitochondrial dysfunction in myotubes. 31 Intraperitoneal glucose injection reduced hepatic FTO mRNA levels in mice, but there were positive correlations between hepatic FTO mRNA expression and gluconeogenic gene expression. 32 This positive correlation was supported by another study, which also demonstrated that FTO mRNA was negatively associated with fat mass in skeletal muscle.…”
Section: Introductionmentioning
confidence: 90%
“…These models include (a) excess ROS production by the mitochondria in experimental murine models of excess nutrient intake and T2D; 2,23,[28][29][30] (b) excess ROS production by NADPH oxidases due to the overactivity of the renin-angiotensin system and increased angiotensin II levels; 31 and more recently (c) excess ROS production by XO in experimental diabetes models. 32 The present review will focus only on excess ROS production according to model (a) above given the abundance of research that has focused on mitochondrial ROS as being implicated in skeletal muscle insulin resistance.…”
Section: Linking Mitochondrial Ros To Skeletal Muscle Insulin Resistancementioning
confidence: 99%
“…32,50,51 In contrast to these findings, Brinkmann et al 52 reported reduced levels of F2-isoprostanes in the skeletal muscle of people with T2D when compared with age and BMI-matched controls.…”
mentioning
confidence: 94%
“…FTO could act as a demethylase of both single-stranded DNA (3-meT) and RNA (3-meU) (35,36 overexpression of FTO in myotubes significantly altered the expression of several genes, particularly those of the mitochondria (23), suggesting that the demethylation activity of FTO on DNA might regulate the expression of metabolic genes, and that dysregulation of this process might participate to obesity and/or T2D phenotype. Interestingly, we observed a transient increase of FTO expression in the early phase of 3T3-L1 differentiation, which coincides with the induction of PPARc2 expression, a key transcription factor involved in adipocyte differentiation.…”
Section: Figure 4 Effect Of Fto Silencing On 3t3-l1 Differentiation mentioning
confidence: 99%